Evaluation of Psychometric Aspects of Cleveland Scale of Activity Daily Living in the Diagnosis of Dementia in Iran - Maryam Noroozian; Zahra Poormand; Vali Allah Farzad; Gholamreza HadJati; Anita Baghdasariyans (Tehran University of Medical Sciences, 2013)
Background: The purpose of this study was to design a valid questionnaire to the Iranian culture for dementia diagnosis and more specifically in its early stage.Methods: A cross-sectional study was conducted in 2012 in Memory Clinic of Roozbeh Hospital and Iranian Alzheimer Association in Tehran in 2012. Among 235 subjects, there were 72 patients with Alzheimer's disease (AD), 137 patients with other types of dementia, and 26 subjects with Mild Cognitive Impairment (MCI), which 107 of them were male. Moreover, 42 healthy subjects were selected as control group. We considered psychometric properties of the Cleveland Scale of Activity Daily Living (CSADL) questionnaire and used standard making operations according to exploratory factor analysis.Results: Three factors were extracted: self-care (21 items), language skills (14 items), and planning (7 items). Convergent validity was 0.86 and cut off point for total, basic and instrumental scores respectively was 20, 3 and 20.Conclusion: It can be claimed that Persian Version of CSADL psychometric questionnaire has appropriate indicators and can serve as a useful tool for research in dementia and in its early stage. It can also enable the implementation of scientific research in academic and medical centers on dementia in general and Alzheimer's disease specifically in Iran.